Case Report: Treatment of chondroblastoma of the first metatarsal bone in children with the induced membrane technique - Li, Zonghuan; Wang, Zheng; Liu, Hong; Zhu, Shaobo (Frontiers in Pediatrics, 2025)
IntroductionChondroblastoma occurring in the metatarsal bone is relatively rare clinically. Its diagnosis is confirmed by pathological examination, and the main treatment is lesion curettage and bone grafting. In this article, we report a case of chondroblastoma of the first metatarsal bone in a child treated with the induced membrane technique and review the relevant literature.Case presentationA 9-year-old female patient presented with swelling and pain at the first metatarsal bone of the left foot one month ago without obvious cause. Imaging examination indicated local bone destruction with expansive growth in the first metatarsal. In the first-stage operation using the induced membrane technique, the lesion was removed and filled with bone cement. In the second-stage operation, the bone cement was removed and autologous fibula bone grafting was performed. Four months later, the bone at the metatarsal site healed well, the child could walk normally, and no tumor recurrence was observed during one-year follow-up. The bone at the fibula donor site also healed well, and no complications such as ankle instability at the donor site were seen.ConclusionChondroblastoma of the metatarsal bone in children is relatively rare. The two-stage operation of fibula transplantation using the induced membrane technique can effectivelybridge metatarsal bone defect.